Some approximation properties of new Kantorovich typeq-analogue of Balazs-Szabados operators - Hamal, Hayatem; Sabancigil, Pembe (Springer, 2020)
In this paper, we define a new Kantorovich typeq-analogue of the Balazs-Szabados operators, we give some local approximation properties of these operators and prove a Voronovskaja type theorem.
Keywords: q-calculus; Bernstein operators; q-Balazs-Szabados operators